EPR spectra and rotation of CH3, CH2D, CHD2, and CD3 radicals in solid H2 - Dmitriev, Yu.A.; Zhitnikov, R.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
EPR spectra of CH3, CH2D, CHD2, and CD3 radicals have been observed in H2 matrix in the temperature range 1.6-4.2 K. The radicals were obtained by condensation on a cold substrate of two gas flows: deuterium mixed with 2 mol % methane passed through a discharge and pure hydrogen avoiding the discharge. The CD3 and CHD2 spectra were found to be a superposition of two spectra: high-temperature and low-temperature. A transformation of the shape of CD3 and CHD2 spectrum with decreasing sample temperature was observed. This is attributed to a change in the populations of the lowest rotational states of the radicals. Compared to known results for deuterated methyl radicals in Ar, the present observations suggest an existence of a hindering barrier for the radical rotation in solid H2.